Present-Day Challenges in Homeschooling Specialists’ Training in Canada - Svyrydova, Tetiana (Educational Challenges, 2021)
The article deals with the results of the recent scientific research concerning training of experts for homeschooling in general and its today’s challenges in particular. Canada has been chosen as a target country due to its specific attitude towards homeschooling and its significant experience in specialist and/or teacher training for homeschooling. The urgency of the problem has recently aggravated because of the present-day situation with covid-19 worldwide restrictions in education and subsequent increase in the number of homeschooling families that need expert advice from certified specialists. The purpose of the article is to highlight the actual state of homeschooling specialist training in Canada in order to decide on a possibility to apply the experience of Canada in those counties which face similar challenges. To conduct the scientific results such methods as a continuous sampling method and a data classification method were used. The present research resulted into revealing current challenges in the realm of teacher training for homeschooling in Canada along with possible ways of overcoming of all the revealed difficulties with the help of various institutions that provide pedagogical education or practical support within the process of specialist training for homeschooling. The article considers acquiring skills and knowledge necessary for organizing family (home) education from colleges, institutes, universities, teacher training courses, associations, homeschooling support groups, etc. Some relevant educational programs provided by these establishments are under consideration as well. Thus, the following conclusions were inferred from the results of the research: the system of Homeschooling Specialists’ Training in Canada is highly-developed and well-prepared to cope with the difficulties connected with the Present-day Challenges.